(untitled) (Journal of Oriental Studies, 2016)
One of the key concepts of cognitive linguistics, our time is the concept of freedom. The concept of freedom with the semanticcognitive perspective has undergone in recent years, major changes related to psychological and mental orientations of carriers of different cultures, which has expanded its semantic and syntactic features. In this paper we attempt to analyze the linguistic means by which introduced the concept of freedom in the minds of Russian and Arabic.